Australian Chamber Music with Piano - Sitsky, Larry (ANU Press, 2011)
This book represents the first critical survey of a section of a rich Australian corpus of chamber music. The author has included various instrumental combinations with piano as well as vocal music with piano. The survey is chronological, as well as by composer. An appendix to the work provides source material for future research into this area. The research has concentrated on progressive modernist music by Australian composers. The commentary utilises the author's rich experience as composer, pianist and educator.